Pengaruh Sudut Kemiringan Terhadap Unjuk Kerja Panel Surya (Studi di Universitas Bangka Belitung) - Rifki Mardani; Rika Favoria Gusa; Asmar Asmar; Wahri Sunanda (Fakultas Teknik Elektro - Universitas Sultan Ageng Tirtayasa, 2022)
In this study, data were collected on solar irradiation (W/m2), short circuit current (Isc), and open circuit voltage (Voc) at angles of 10°, 20°, 30°, 40°, 50°, and 60°. The research method used is an experimental method of data collection with variations in the tilt angle of the solar panels. From the results of research that was tested using monocrystalline solar panels with a capacity of 50 WP, it can be concluded that the highest value of the solar panel output power (Pout) was 31.59 Watts at an angle of 10° which occurred at 01.00 p.m. Then the highest efficiency value (η) of 15.47% occurred at 03.00 p.m. with a slope angle of 10º.